Michel Foucault and the history of economic thought - Nicolas Vallois (Œconomia, 2015)
Michel Foucault dedicated a significant part of his works to the study of political economy. In the late 1980s, these analyses attracted the interest of historians of economic thought (Amariglio, 1988, 1900; Birken, 1990). The primary purpose of this article is to provide a review survey of Foucault’s reception among historians of economic thought. Reading and interpreting Foucault is not straightforward. In reflecting on his work, Foucault refused to consider himself an “author” who could be characterized by a single, consistent framework. However, he elaborated a coherent historiographical method which we characterize as politically engaged journalism. The principles of that method allow us to identify two common confusions in interpretations of Foucault’s work. First, advocates of Foucault in the history of economic thought literature consider him a “heterodox economist” who would be opposed to “mainstream economics”. However, Foucault did not intend to criticize economic theories in this particular sense. The second source of confusion involves interpreting Foucault as a sociologist interested in the analysis of power, or a social historian, although he rejected context-based historiographical approaches. We would suggest that Foucault she be considered more a “postmodernist philosopher” than a historian of economic thought per se. In this respect, the association of “Foucauldian theory” with postmodernism is a major distortion in his reception by historians of economic thought.